Inwardness and commodification: how romanticist hermeneutics prepared the way for the culture of managerialism - a theological analysis - Wannenwetsch, B (SAGE Publications, 2008)
This essay undertakes a theological genealogy of the spirit of managerialism as it affects churches today by tracing it back to hermeneutical shifts in the history of (Protestant) theology: the loss of the externality of the word as a result of Schleiermacherian hermeneutics as it moved the centre of attention from a doctrine of the word to a doctrine of faith. The author demonstrates how the shift to inwardness created the conditions in which the market of 'spiritual needs' could emerge that today's church managers capitalize on. Theological analysis is embedded in a narrative account of an instructive controversy in the German Protestant churches in the 1990s when a group of theologians produced a manifesto 'Against the Economisation of the Church'.